Real-Life Data on Sofosbuvir/Ledipasvir in Patients with Chronic Viral Hepatitis C Genotype 1b: A Single-Center Experience - Coşar, Arif Mansur; Durak, Serdar (Turkish Journal of Gastroenterology, 2022)
Background: The course of hepatitis C disease has changed with the use of direct-acting antiviral drugs in the treatment of the disease.The aim of this study was to evaluate the real-life efficacy and safety of the sofosbuvir/ledipasvir drug regimen in the treatment ofpatients with genotype 1b.Methods: Treatment-naive or -experienced 49 genotypes 1b patients treated with sofosbuvir/ledipasvir participated in the study.Laboratory and hepatitis C virus RNA values were evaluated at baseline, week 12, and week 24 of treatment (36th week for those whoreceived 24 weeks of treatment).Results: The sustained virologic response rate was 100% in patients who completed treatment. At the end of the study, there wasa significant decrease in alanine transaminase, aspartate transaminase, gamma-glutamyl transferase, and alpha-fetoprotein levels(P = .000014, P = .000581, P = .000012, and P = .000821), respectively. Renal function tests (creatinine, estimated glomerular filtrationrate) worsened (P = .003 and P = .007, respectively). Hepatocellular carcinoma (HCC) was developed in 2 patients during post-treatmentfollow-up. In Kaplan–Meier analysis, the probability of not developing HCC was 86.5% at 26 months.Conclusion: The sofosbuvir/ledipasvir combination is effective in treating genotype 1b chronic hepatitis C with high sustained virologicresponse rates. Because there are few drug interactions, it may be a suitable option for patients taking multiple medications or whoare transplant recipients. Renal function should be monitored closely during and after treatment, as there is a risk of worsening renalfunction after treatment.